Membangun Dunia Aman : Strategi Perlindungan Anak dari Kekerasan (International Forum of Researchers and Lecturers, 2025)
Violence against children is a serious problem that affects their physical, mental, and emotional development. In an effort to protect children from violence, a comprehensive and integrated strategy is needed. This article discusses various approaches that can be applied, including education and increasing public awareness of children's rights, strengthening protection policies, and providing psychosocial support for victims. In addition, the importance of training for parents and educators in positive parenting, as well as community involvement in violence prevention, is also outlined. Cross-sector collaboration between government, non-governmental organizations, and communities is key to creating a safe and supportive environment for children. By implementing technology to facilitate reporting and handling of cases, it is hoped that this strategy can reduce the prevalence of violence against children and ensure a safer future for future generations.